(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
This research is related to the implementation of religious moderation through interfaith and cultural proselytizing courses in the Islamic communication and broadcasting study program at the Faculty of Da’wah and Communication UIN SU Medan. The purpose of this study was to see the implementation of religious moderation in higher education, and to see the implementation of religious moderation in interfaith and cultural proselytizing courses. The approach used in this lamp is a qualitative approach, with a literature research design. The results showed that the implementation of religious moderation in the interfaith and cultural Da’wah course was contained in discussions related to religious harmony and tolerance between religious people